Hubungan Ketepatan Switch Therapy Terhadap Kesembuhan Luka, Lama Rawatan dan Biaya Pengobatan Antibiotik Pasien Appendisitis - Lathvi Masyithah; Armenia Armenia; Almahdy Almahdy (Fakultas Farmasi Universitas Andalas, 2016)
Antibiotic Switch therapy is defined by the switch of intravenous antibiotic therapy to oral form. This research aimed to learn about the relationship of switch therapy toward the value of wound healing, lenght of stay and the antibiotic expenditure. The data of this cross sectional study was collected from medical record and by direct investigation to patients for their macroscopis the wound healings value. T-test was used to compared the relationship of the patient wound healings value, lenght of stay and the antibiotic expenditure between the those with and accurate switch therapy and those without it. The result showed that there was no different of wound healing value between those groups of patients (P>0,1). On the other hand, lenght of stay and antibiotic expenditure of the patient with the accurate switch therapy was cuted on the patient with the accurate switch therapy. These indicated that accuracy of switch therapy will proceed a benefit outcome to the patient with appendicitis, especially to there lenght of stay and antibiotic expenditure as well.